Robust parameter design using the weighted metric metod - The case of "the smaller the belter" - Ardakani, Mostafa Kamali; Noorossana, Rassoul; Niaki, Seyed Taghi Akhavan; Lahijanian, Homayoun (Zielona Góra: Uniwersytet Zielonogórski)
In process robustness studies, it is desirable to minimize the influence of noise factors on the system and simultaneously determine the levels of controllable factors optimizing the overall response or outcome. In the cases when a random effects model is applicable and a fixed effects model is assumed instead, an increase in the variance of the coefficient vector should be expected.
Keywords: multiobjective decision making; regression estimation; response surface methodology; robust parameter design; weighted metric method